Experiential and Outdoor Learning in the Transition to University Courses—The Mathematics Case. Issue 2 (7th February 2023) - Penazzi, Davide; McCready-Fallon, Joseph; Rosser, Sharon
Abstract : Student retention is a priority in universities, as drop-out rates among university students within 12 months of starting continue to rise, according to UK figures released by the Higher Education Statistics Agency (HESA) (https://www.hesa.ac.uk/data-and-analysis/performance-indicators/non-continuation, accessed February 2022), and with approximately a quarter of freshmen not enrolling for a second year in the US (NSC Research Centre. 2020. Persistence and Retention . Snapshot report. https://nscresearchcenter.org/wp-content/uploads/PersistenceRetention2020.pdf, accessed 1 June 2021). The transition to university, and in particular to a mathematics degree, is a challenging period for many students. Several methods to support HE students through this initial stage have been developed across the years, mostly designed in and for academic settings. This paper will describe an innovative approach, beyond the traditional classroom, which involves a three-day residential course tailored specifically to support the transition of mathematics students into HE, examining its implementation into the BSc Mathematics and MMath degree programs and its effectiveness with first-year Mathematics students at the University of Central Lancashire. The results provide an evaluation of this intervention over four years, showing the positive impact on attainment, together with increased student participation and engagement.